New Convenient Synthesis of Fluorescent 1,8-Naphthyridines and the Metal-Sensing Properties of the Dyes - Goel, Atul; Nag, Pankaj; Umar, Shahida (Synlett, 2014)
A new and efficient approach to a series of highly fluorescent non-aggregating donor–acceptor 1,8-naphthyridines is described. Examination of the photophysical properties of the 1,8-naphthyridines revealed that the presence of donor–acceptor functionality leads to bright green fluorescence with solvatochromism in solvents of differing polarities. The application of these molecules in metal sensing was also explored.
Keywords: 1,8-naphthyridines; lactones; non-aggregating; solvatochromism; metal sensing